2003
DOI: 10.1152/ajplung.00123.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia-induced NAD(P)H oxidase activation and regulation by MAP kinases in human lung endothelial cells

Abstract: Hyperoxia increases reactive oxygen species (ROS) production in vascular endothelium; however, the mechanisms involved in ROS generation are not well characterized. We determined the role and regulation of NAD(P)H oxidase in hyperoxia-induced ROS formation in human pulmonary artery endothelial cells (HPAECs). Exposure of HPAECs to hyperoxia for 1, 3, and 12 h increased the generation of superoxide anion, which was blocked by diphenyleneiodonium but not by rotenone or oxypurinol. Furthermore, hyperoxia enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
187
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(196 citation statements)
references
References 59 publications
8
187
1
Order By: Relevance
“…Although previous studies demonstrated that p38 activity is associated with nitrogen oxide and other oxidants, 22,25,44 no direct evidence has shown a particular link of p38 to hyperoxic toxicity in lung epithelial cells. In this study, cells expressing hOgg1 or vector control were exposed to room air or hyperoxia for 36 h. Phosphorylated p38 was quantitatively measured using phospho-ATF-2 Thr71 antibody in A549 cells after immunoprecipitation with immobilized phospho-p38 antibodies (Thr180/Tyr182).…”
Section: Hogg1 On P38 Activation Induced By Hyperoxiamentioning
confidence: 90%
“…Although previous studies demonstrated that p38 activity is associated with nitrogen oxide and other oxidants, 22,25,44 no direct evidence has shown a particular link of p38 to hyperoxic toxicity in lung epithelial cells. In this study, cells expressing hOgg1 or vector control were exposed to room air or hyperoxia for 36 h. Phosphorylated p38 was quantitatively measured using phospho-ATF-2 Thr71 antibody in A549 cells after immunoprecipitation with immobilized phospho-p38 antibodies (Thr180/Tyr182).…”
Section: Hogg1 On P38 Activation Induced By Hyperoxiamentioning
confidence: 90%
“…The effect of oxidative stress on endothelial cells and VSMC include direct oxidation of proteins and indirect modulation of kinase pathways such as PKC, ERK, Src, and Pho [9]. Many factors such as cytokine, drugs, and extracellular inflammation factors could increase ROS generation to regulate cellular reactions including cell proliferation and migration [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since the activation of MAPKs can be triggered by oxidative stress [9] and chlorotyrosine can increase superoxide anion production in this study, we further investigated whether chlorotyrosine could activate MAPKs. Major MAPKs include ERK1/2, and the c-Jun Nterminal protein kinase (JNK), and p38.…”
Section: Chlorotyrosine Activates Erk1/2 But Not Jnk or P38mentioning
confidence: 99%
See 1 more Smart Citation
“…These NOX's appear to control several vascular processes, such as vascular tone, vascular cell growth and angiogenesis, and inflammation. Accordingly, pulmonary endothelial cells have been demonstrated to generate NADPH-derived oxidants in response to pulmonary ischemia (178,179) as well as hyperoxia (180), which is associated with membrane depolarization due to the activation of K(ATP) channels, and resulting in stimulated endothelial cell proliferation and NO production (178,181,182). Although these responses were in some cases inhibited by catalase, suggesting the involvement of H 2 O 2 (182), recent studies also suggest a role for O 2 •− in endothelial NOX signaling (77).…”
Section: Functional Aspects Of Nox In Other Lung Cell Typesmentioning
confidence: 99%